2023
DOI: 10.1136/bmjopen-2022-061315
|View full text |Cite
|
Sign up to set email alerts
|

Systematic scoping review of interventions to prevent and respond to child marriage across Africa: progress, gaps and priorities

Abstract: ObjectivesDespite the high prevalence of child marriage in Africa, little is known about the current state of the evidence on interventions to prevent and respond to child marriage in the region. The objectives of this systematic scoping review are to describe the breadth of existing evidence on child marriage prevention and response interventions, analyze where these interventions have been implemented, and identify research gaps and priorities for moving forward.MethodsThe inclusion criteria incorporated pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In Western province, these dynamics lead more often to pregnant girls being kept in the family, while pregnant girls in Eastern province are more likely to be married off. While the issue of shame is hardly directly addressed, we found that child marriage programming over the years has shifted towards focusing on girls' development, preferences, and decisions, moving away from viewing them solely as victims of parental and spousal pressures (45).…”
Section: Welfare Assessment (Pmt)mentioning
confidence: 87%
See 4 more Smart Citations
“…In Western province, these dynamics lead more often to pregnant girls being kept in the family, while pregnant girls in Eastern province are more likely to be married off. While the issue of shame is hardly directly addressed, we found that child marriage programming over the years has shifted towards focusing on girls' development, preferences, and decisions, moving away from viewing them solely as victims of parental and spousal pressures (45).…”
Section: Welfare Assessment (Pmt)mentioning
confidence: 87%
“…Among 132 African child marriage interventions reviewed, 38 publications focusing on educational interventions, particularly targeting unmarried girls, emphasized the importance of increasing enrolment, retention, completion, and transition rates (i.e. from primary to secondary school) for girls' schooling to delay marriage (45). Looking at interventions addressing education more broadly, the Zambian School Re-Entry Policy from 1997 for adolescent mothers to return to school is crucial in preventing child marriage.…”
Section: Interventions Addressing Educationmentioning
confidence: 99%
See 3 more Smart Citations